Pelatihan Pengelolaan Dan Pengolahan Data Hasil Pengisian Google Form Pada Jaringan Pemuda Dan Remaja Masjid Indonesia Jakarta Selatan - Eko Setia Budi; Eva Zuraidah; Besus Maula Sulthon; Ipin Sugiyarto; Agustin Ria Pratiwi; Ahmad Anshori Ardani; Melati; Fadila S Ismail; Ahmad Fio Nugraha (Akademi Farmasi YPPM Mandiri, 2022)
Due to the Covid-19 pandemic, work cannot be done at home, it is intended to reduce the number of people exposed to Covid-19. Likewise with the activities carried out by the South Jakarta Indonesian Mosque Youth and Youth Network. Indonesian society is very adaptive to the progress of information and communication technology development, now there are many modern facilities available to facilitate access to information, including the presence of Google Forms (google form) as an innovation to collect data and information from Google's corporate platform and manage and process it. google forms data. Likewise, the administrators of the South Jakarta Jakarta Indonesian Mosque Youth and Youth Network (JPRMI) who have to adapt to current developments in making activity reports, because they have to report these activity reports online. Based on these reasons, Nusa Mandiri University held a socialization on the Management and Processing of Google Forms for Reporting Management Activities. The administrator of the Indonesian Mosque Youth and Youth Network is a group of young men and women. After the group is formed, one person is appointed who has the responsibility as chairman. This socialization aims to introduce one of the facilities for managing and processing Google Forms that can facilitate reporting of activities that have been carried out by the management of JPRMI Ragunan. The result of the implementation of this community service activity is that participants in the activity acquire new knowledge in managing and processing Google Forms.